Jual Beli yang Dilarang (Fasid/Bathil) dalam Pandangan Hukum Islam - Siswadi, Siswadi; Najihah, Wilda Ainun (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2023)
In daily life, humans are social creatures who need each other in various ways, including carrying out economic activities in order to fulfill their daily needs. It is impossible for humans to be social creatures who can fulfill their life needs alone, considering the many and varied needs themselves. Human limitations will encourage them to relate to each other to fulfill their needs, either by working together, exchanging goods or by buying and selling and so on. Buying and selling activities are routine activities carried out every time by all humans. However, not all Muslims carry out correct buying and selling according to Islamic law. There are even those who do not know at all about the provisions stipulated by Islamic law in terms of buying and selling (business). In Islamic law sources there are many examples or regulations for correct business according to Islam. Not only for sellers but also for buyers. Nowadays, more sellers prioritize individual profits without being guided by the provisions of Islamic law. They only seek worldly profits without expecting blessings from what they have done. The pillars of buying and selling include three things, namely: there must be an akid (the person making the contract), ma'qud alaihi (the thing being contracted) and shighat, which consists of ijab (offer) qabul (acceptance) A fake sale and purchase is a contract in which one of the terms and conditions are not fulfilled perfectly, such as a seller who is not competent, goods that cannot be handed over and so on. Meanwhile, a fasid sale and purchase is a contract that fulfills the conditions of harmony